Destination management organizations as interface between destination governance and corporate governance - Pechlaner, Harald; Volgger, M.; Herntrei, M. (2012)
Destination management organizations (DMOs) play a major role in managing destination networks and in fostering cooperation between destination actors. DMOs are central figures in the governance of tourism destinations. However, being organizations, their operations are also judged according to their organizational efficiency and effectiveness. This paper applies the concept of corporate governance to capture these internal performance indicators, and investigates its relationship to the external performance of DMOs as promoters of cooperation. Very few studies have considered such inter-dependencies between DMO performance and destination performance; and even fewer have explicitly analysed the relationships between the destination governance and the corporate governance of DMOs. Therefore, this research uses an exploratory, theory-generating case study approach to develop testable hypotheses for future generalizing research attempts. Semi-structured interviews were conducted with several destination actors, and qualitatively analysed using the GABEK toolset. From this qualitative analysis four hypotheses emerged, which generally indicate a positive link between a DMO's corporate governance characterized by a broad stakeholder involvement, an efficient way of working, visible signs of performance on the one hand, and both the DMO acceptance and the level of cooperation in the destination on the other hand. © 2012 Taylor & Francis.